2009
DOI: 10.1007/s11302-009-9134-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the R276A gain-of-function mutation in the ectodomain of murine P2X7

Abstract: The cytolytic P2X7 purinoceptor is widely expressed on leukocytes and has sparked interest because of its key role in the activation of the inflammasome, the release of the pro-inflammatory cytokine IL-1β and cell death. We report here the functional characterisation of a R276A gainof-function mutant analysed for its capacities to induce membrane depolarisation, calcium influx and opening of a large membrane pore permeable to YO-PRO-1. Our results highlight the particular sensitivity of R276A mutant to low mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Although the sites directly participating in ATP binding are conserved among subtypes, the affinities for ATP are quite distinct among different subtypes [59]. Based on mutagenesis studies on P2X7 receptors, residues around the ATP binding sites are likely to contribute to the sensitivity to ATP [60,61]. Our study showed that the positions analogous to K145 and R276 in Rno-p2x7 are conserved within subtypes ( Table 1).…”
Section: Mmu-p2x1mentioning
confidence: 73%
“…Although the sites directly participating in ATP binding are conserved among subtypes, the affinities for ATP are quite distinct among different subtypes [59]. Based on mutagenesis studies on P2X7 receptors, residues around the ATP binding sites are likely to contribute to the sensitivity to ATP [60,61]. Our study showed that the positions analogous to K145 and R276 in Rno-p2x7 are conserved within subtypes ( Table 1).…”
Section: Mmu-p2x1mentioning
confidence: 73%
“…Regardless of the mechanism by which the difference in ATP sensitivity occurs (an effect on ATP binding affinity or gating), an attractive hypothesis would be that the absence of the arginine in P2X1R and P2X3R influence at least partially ATP sensitivities. Although this point deserves to be addressed for P2X1 and P2X3, a recent work has shown that mutating Arg 276 in murine P2X7 (corresponding to Arg 274 in rP2X2) into alanine also resulted in a gain-of-function phenotype (32). Finally, a natural polymorphism exists for this residue in human P2X7, although its phenotype is still undefined (33), emphasizing this region as a potential target for allosteric regulation of human P2XR.…”
Section: Discussionmentioning
confidence: 99%
“…The positive charge of Lys145 is present in all the mammalian P2X7Rs (Figure 1) and may facilitate agonist access or binding to the ATP-binding site. In contrast, the charge-neutralizing R276A mutation in the mouse P2X7R increased the sensitivity to ATP and BzATP, as revealed by agonist-induced increases in the cytosolic Ca 2+ level and YO-PRO-1 uptake, and also slowed the open channel deactivation (Adriouch et al, 2009). However, the charge-conserving R276K mutation and, similarly the R277K mutation, enhanced ATP-induced increases in the cytosolic Ca 2+ level and YO-PRO-1 uptake without affecting the agonist sensitivity (Adriouch et al, 2008, 2009).…”
Section: An Overview Of the Structure-function Relationshipsmentioning
confidence: 99%
“…In contrast, the charge-neutralizing R276A mutation in the mouse P2X7R increased the sensitivity to ATP and BzATP, as revealed by agonist-induced increases in the cytosolic Ca 2+ level and YO-PRO-1 uptake, and also slowed the open channel deactivation (Adriouch et al, 2009). However, the charge-conserving R276K mutation and, similarly the R277K mutation, enhanced ATP-induced increases in the cytosolic Ca 2+ level and YO-PRO-1 uptake without affecting the agonist sensitivity (Adriouch et al, 2008, 2009). The NS-SNP R276H mutation increased (or H276R reduced as described in the original study) ATP-induced ethidium uptake (Stokes et al, 2010).…”
Section: An Overview Of the Structure-function Relationshipsmentioning
confidence: 99%